2019
DOI: 10.1093/mnras/stz1567
|View full text |Cite
|
Sign up to set email alerts
|

Radio emission from the unbound debris of tidal disruption events

Abstract: When a star gets too close to a supermassive black hole, it is torn apart by the tidal forces. Roughly half of the stellar mass becomes unbound and flies away at tremendous velocities -around 10 4 km/s. In this work we explore the idea that the shock produced by the interaction of the unbound debris with the ambient medium gives rise to the synchrotron radio emission observed in several TDEs. We use a moving mesh numerical simulation to study the evolution of the unbound debris and the bow shock around it. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 44 publications
(52 reference statements)
0
40
2
Order By: Relevance
“…Compared to the primary ejecta unbound as an immediate consequence of the disruption (Guillochon et al 2016;Krolik et al 2016;Yalinewich et al 2019), this secondary ejecta has a fraction ≈ f u of the mass, higher velocity ( §4.4), and a larger opening angle ( §4.1). The ejecta drives a bow shock while running into the surrounding medium, and relativistic electrons accelerated in this shock can produce synchrotron radiation (Krolik et al 2016;Yalinewich et al 2019). At later times, the shock driven by the ejecta may mimic a supernova remnant (Guillochon et al 2016).…”
Section: Energeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the primary ejecta unbound as an immediate consequence of the disruption (Guillochon et al 2016;Krolik et al 2016;Yalinewich et al 2019), this secondary ejecta has a fraction ≈ f u of the mass, higher velocity ( §4.4), and a larger opening angle ( §4.1). The ejecta drives a bow shock while running into the surrounding medium, and relativistic electrons accelerated in this shock can produce synchrotron radiation (Krolik et al 2016;Yalinewich et al 2019). At later times, the shock driven by the ejecta may mimic a supernova remnant (Guillochon et al 2016).…”
Section: Energeticsmentioning
confidence: 99%
“…The denser medium around AGNs could mean that TDEs are more radio-bright in AGNs than in vacuum. The prompt emission due to the secondary ejecta could be more luminous than the primary ejecta because the fastest material has higher velocity and a wider interaction area (Krolik et al 2016;Yalinewich et al 2019). All these may explain why the radio transient Cygnus A-2 (Perley et al 2017), if interpreted as a thermal TDE happening in an AGN (de Vries et al 2019), is brighter in radio than typical thermal TDEs in vacuum.…”
Section: Energeticsmentioning
confidence: 99%
“…The TDE Arp 299-B AT1 was initially detected as a near-infrared transient; radio verylong baseline interferometry (VLBI) resolved a relativistic TDE-driven jet (Mattila et al 2018). More recently, the thermal TDEs ASASSN-14li (Alexander et al 2016;Krolik et al 2016;van Velzen et al 2016;Yalinewich et al 2019) and XMMSL1 J0750-85 (Alexander et al 2017) were found to have radio emission that indicated sub-/nonrelativistic outflows, indicating that these are the first thermal TDEs with detected radio emission. These objects revealed the possibility that all TDEs are accompanied by radio emission, with earlier nondetections (Bower 2011;Bower et al 2013;van Velzen et al 2013;Arcavi et al 2014;Chornock et al 2014) a result of their lower radio luminosities: both ASASSN-14li and XMMSL1 J0750-85 were relatively nearby at z0.02, whereas the median TDE redshift is approximately z∼0.1 (Komossa 2015)-though see Blagorodnova et al (2017) and Saxton et al (2019) for upper limits on the radio luminosities of TDEs that are more than an order of magnitude below that of ASASSN-14li in hosts that are similarly nearby.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting application of moving mesh codes has been done by Yalinewich et al (2019), who simulate the evolution of the unbound debris and the associated radio emission.…”
Section: Moving Mesh Codesmentioning
confidence: 99%